Awful parenthesis : suspension and the sublime in romantic and Victorian poetry - McCarthy, Anne C. (University of Toronto Press, 2018)
Examining various aesthetics of suspension in the works of nineteenth-century poets such as Coleridge, Shelley, Tennyson, and Christina Rossetti, Anne C. McCarthy shares important insights into the cultural fascination with the sublime.